The role of clinical-functional research in case of pneumoconiosis associated with chronic obstructive pulmonary disease in workers of mining and metallurgical industry. - R. V. Rubtsov (Medičnì Perspektivi)
The purpose of the research is to study the features of clinical symptoms (using standard questionnaires),  the nature of external respiration disorders according to the spirometry indices in workers of mining and metallurgical industry with pneumoconiosis associated with COPD. The article presents the data of clinical examination of 634 workers with lung pathology of occupational etiology:  I group included 98 workers with pneumoconiosis associated with COPD, II group included 21 workers with pneumoconiosis, and III group – 515 workers with COPD of occupational etiology. A comparative analysis of clinical symptoms and external respiration function (ERF)  indicators was conducted. It has been revealed that for pneumoconiosis associated with COPD the most informative are indicators of Disease Assessment Test, exceeding 11 points, as well as spirometric volumetric and speed indicators of expiration, indicating combination of obstructive and restrictive disorders of ERF: lung vital capacity  (LVC) less than 67.0%, forced lung vital capacity  (FLVC) less than 60.0%, peak expiratory flow rate less than 40.0%, increase of the forced expiration volume (FEV1) index after the conducted (bronchodilation test) BDT less than 16.1%. The etiologic proportion of the influence of these indicators ranges from 40.5 to 71.6%, the sensitivity is from 0.22 to 0.39, the conditional possibility of occurrence is from 0.6 to 0.94, and the background capability is from 0.17 to 0.35. The revealed diagnostic criteria allow to carry out timely diagnostics, to determine treatment tactics and prevent PC associated with COPD in workers of mining and metallurgical industry.